Między powieścią a adaptacją – kilka spostrzeżeń z perspektywy widza - Sulejewska, Justyna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
Between Story and Film Adaptation: A Few Insights From a Viewer The essay is an attempt to analyze the mechanisms of adaptation based on the example of Enemy (2013) by Denis Villeneuve. It also confronts the director’s formal choices with an individual viewer’s expectations. The text presents similarities and differences between the novel (The Double, José Saramago) and the movie. The author also points out film-like features of the book. Aspects of the original story were not developed by the filmmakers, and this changed the meaning of the film.